(untitled) (International Journal of Engineering and Computer Science, 2014)
Data transmission in real time environment has been invoked by trustworthy persons as well as in internet media it resides on secure communication channel. The introduction of internet increases security issue twice for exchanging the information electronically. Cryptography is the process of scrambling the data into unknown format. This process is done with the help of encryption & decryption algorithm. The basic two ideas behind the cryptographic techniques are substitution & transposition. The Caesar cipher substitution method is used to alter the plaintext characters with the help of automatic key. This paper presents a multi stage encryption algorithm. At the end of each stage an intermediate cipher is produced. The transposition is employed by using crossover method of genetic algorithm. Final ciphertext is derived from the combined effect of basic arithmetic & logic operations.